Bilingual and Multilingual Legal Dictionaries: New Standards for the Future - Šarčević, Susan (Revue générale de droit, 1988)
Alarmed by the notorious inaccuracy of “traditional” bilingual and multilingual legal dictionaries, legal lexicographers began experimenting with new methods of improving user reliability about 15 years ago. Analyzing numerous bilingual and multilingual legal dictionaries of various languages (combinations of English, French, German, Spanish, Italian, Dutch and Chinese), the author claims that one can now speak of a special methodology of legal lexicography which has set new standards for the future.Focusing on the problems of interlingual transfer in the field of law, the author deals with the problem of equivalence, pointing out that, in the majority of cases, the functional equivalents of different legal systems are only partially equivalent. This has led to the need to measure the degree of their equivalence in order to determine their acceptability in dictionary entries. For this purpose, methods of comparative conceptual analysis can be used. Moreover, bilingual legal dictionaries are now equipped with a more or less elaborate documentary apparatus including definitions of both the source term and its equivalent, contextual data and geographic information on the usage of target language variants.In conclusion, the question is raised as to the role of dictionaries in the standardization of legal terminology at the national level (Canada), the regional level (EEC, CMEA) and at the international level (UN).